INFORMATION TECHNOLOGY AND THEIR IMPACT ON MATH EDUCATION - ORSZAGHOVA, Dana (Trends in education, 2013)
Information technology (IT) as a major phenomenon of the information society has become the part of the university education and their tools are used in a variety of ways. The impact of IT is reflected on the educational process, inter alia, we can see changes in the competences and tasks of the students and educators. Teachers use IT tools to support the active participation of students in education, to create the electronic educational resources and to apply them in the study of mathematics. In the paper we present the experience from the pedagogical process at the Slovak University of Agriculture in Nitra, where teachers from the Department of Mathematics actively use methods and IT means in e-learning.
Keywords: mathematics; mathematics education; information technology; computerization of society; e-learning